Kolaborasi Kebijakan Pemerintah dalam Mengurangi Penyelundupan di Daerah Perbatasan (Studi Kasus Republik Indonesia & Republik Demokratik Timor Leste) - Rokhanyah, Hesti; Noor, M. Ilham Nazaruddin; Harahap, Ali Musa; Wijaya, Bagas Sagita; Amalia, Novi Rizka (Jurnal Pemerintahan dan Politik, 2023)
This study analyzes the collaborative efforts between Indonesia and Timor-Leste to reduce smuggling along their border regions. This qualitative research employs a document study technique, involving the analysis of secondary data obtained from books, journals, websites, and reports and this study utilizes the concepts of Border Diplomacy and International Cooperation. In pursuit of this objective, both countries have implemented border diplomacy to define their national boundaries and foster economic cooperation and cross-border collaboration to strengthen diplomatic relations and promote economic development in the border regions between the two nations. International cooperation in the border region encompasses various sectors, including the economic, social, and cultural realms, aimed at addressing issues such as smuggling. The Border Liaison Committee (BLC), led by the Vice Governor of NTT, serves as Border Liaison Committee and is responsible for coordinating social, economic, and cultural activities to enhance well-being and security in the border areas. Additionally, security cooperation in the border region involves the Indonesian National Police (POLRI) and the Timor-Leste National Police (PNTL) with the goal of addressing illegal entry, smuggling, and cross-border criminal activities. Lastly, the development of Border Crossing Posts (Pos Lintas Batas Negara - PLBN), such as PLBN Mota’ain, PLBN Wini, and PLBN Motamasin, had a significant impact on security, border, the economy, and surveillance between two countries.